If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(3x + 2) = 62 Reorder the terms: 7x + -1(2 + 3x) = 62 7x + (2 * -1 + 3x * -1) = 62 7x + (-2 + -3x) = 62 Reorder the terms: -2 + 7x + -3x = 62 Combine like terms: 7x + -3x = 4x -2 + 4x = 62 Solving -2 + 4x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = 62 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 62 + 2 4x = 62 + 2 Combine like terms: 62 + 2 = 64 4x = 64 Divide each side by '4'. x = 16 Simplifying x = 16
| 8/5m=4/15 | | 45/?=13 | | 8x+4=13+6x | | In(x+5)+(x-5)=(4x+7) | | 8/9-1/8 | | f(7)=4/49= | | v-5=12 | | 2x-10=6x^1 | | 12x^2-43x+35= | | 3y-26=55 | | 3-19=2z+6z | | 2x-10=6x^2 | | 5x=4x-80 | | -7x-3+1=3.8 | | -107-8x=-17x+19 | | 4(a+2)=2a(a+6) | | 6x=y-8 | | 3x-4=2z+7 | | (2-3y)(5y+1)= | | X+4*3=51 | | 10-3n=55 | | -9(x+3)+5(3x-7)=5(x-6)+9 | | 2y=-70+64 | | b=1/2ps | | -3(k+1)-k-8=4(k+4)+5 | | 5p-8=10p-28 | | 14x+4=9x-11 | | 3x-7+9-2=x+2 | | 4b-3a=8b | | Y^2-225= | | 5x+22=7x+32 | | 12x-24=4x+8 |